2017
DOI: 10.1016/j.prevetmed.2017.05.011
|View full text |Cite
|
Sign up to set email alerts
|

VacciCost – A tool to estimate the resource requirements for implementing livestock vaccination campaigns. Application to peste des petits ruminants (PPR) vaccination in Senegal

Abstract: Vaccination is one of the main tools currently available to control animal diseases. In eradication campaigns, vaccination plays a crucial role by reducing the number of susceptible hosts with the ultimate goal of interrupting disease transmission. Nevertheless, mass vaccination campaigns may be very expensive and in some cases unprofitable. VacciCost is a tool designed to help decision-makers in the estimation of the resources required to implement mass livestock vaccination campaigns against regulated diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…Prior studies suggest that under ideal circumstances it will take a novice rabies control program approximately 6 years to develop capabilities to reach 70% dog vaccination coverage. Tools that aid vaccination campaign managers to design more cost-effective and efficient campaigns, such as what is described here, can minimise the time and cost to achieve canine rabies elimination [23, 36, 37]. …”
Section: Discussionmentioning
confidence: 99%
“…Prior studies suggest that under ideal circumstances it will take a novice rabies control program approximately 6 years to develop capabilities to reach 70% dog vaccination coverage. Tools that aid vaccination campaign managers to design more cost-effective and efficient campaigns, such as what is described here, can minimise the time and cost to achieve canine rabies elimination [23, 36, 37]. …”
Section: Discussionmentioning
confidence: 99%
“…The estimates from Tago et al (Tago et al, 2017) based on a model parameterised with data from Senegal ranged from 0.20 USD (95%CI 0.18-0.21) to 0.34USD (95%CI 0.24-0.54) per dose depending on the assumptions made on number of animals vaccinated per day. These estimates are similar to those reported in this study although they did not consider the opportunity costs of the farmers and the model was mostly parameterised from expert opinion.…”
Section: Discussionmentioning
confidence: 99%
“…In the pastoral system it was field delivery, while in the mixed crop-livestock system it was farmer’s time. Tago et al (Tago et al, 2017) also reported the relative contribution of different cost components. Under high productivity scenarios the largest contributor was “injection supplies” followed closely by the cost of vaccine and staff.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means a vaccine may cause some adverse side effects (e.g., anaphylaxis, decrease in production traits) to a recipient [ 2 , 3 ]. Third, mass vaccination campaigns can be very expensive and may be unprofitable for some livestock farmers [ 84 ].…”
Section: Farm Animal Diseases: Influence Prevalence and Controllmentioning
confidence: 99%